Functional lignin-SiO2 hybrids as potential fillers for phenolic binders. Issue 10 (18th May 2016) - Strzemiecka, Beata; Klapiszewski, Łukasz; Matykiewicz, Danuta; Voelkel, Adam; Jesionowski, Teofil
Abstract: Functional lignin-SiO2 hybrid fillers were synthesized and characterized with a view to their potential application in binders for phenolic resins. The properties of these fillers and of composites obtained from them with phenolic resin were compared with those of systems with lignin or silica alone. The chemical structure of the materials was investigated by Fourier transform infrared spectroscopy. Surface properties of lignin-SiO2 fillers were tested using inverse gas chromatography (IGC). IGC was used for determination of surface energy and surface heterogeneity of the studied fillers. IGC made it possible to assess the adhesion between the tested fillers and phenolic resins. Interactions of functional fillers with phenolic resins were also evaluated by IGC. The results indicated that lignin-SiO2 interacted strongly with the phenolic resin, more strongly than pure lignin. This was proved by SEM observations: thanks to the stronger interactions of lignin-SiO2 hybrid with phenolic resins, a more homogeneous composite was obtained. Thermo-mechanical properties of lignin–silica and resin systems were investigated by DMTA. DMTA results showed that phenolic binders with lignin-SiO2 fillers have better thermo-mechanical properties than systems with lignin or silica alone: higher glass transition temperature and a smaller decrease in storage modulus. Lignin fillers can thus provide new, promising properties for a phenolic binder combining the good properties of lignin as a plasticizer and of silica as a filler improving mechanical properties.